La planificación del bloque de juegos del plan curricular del área de cultura física y su incidencia en la enseñanza de los fundamentos básicos del fútbol en los alumnos de octavo año de educación general básica de los colegios fiscales urbanos Adolfo Valarezo, y Manuel Cabrera Lozano de la ciudad de Loja período 2012 – 2013 - Feraud Valencia, Carlos Alfredo (2014)
This research raises the following issue, as the small block planning curriculum Games Area Physical Education affects teaching the fundamentals of soccer in eighth children of basic education in urban schools Adolfo Valarezo tax and Manuel Cabrera Lozano City Loja period 2012 - 2013 , the objectives have; analyze the incidence of planning block games in teaching the basic fundamentals of soccer in the eighth- basic urban public schools of Loja, the specific objectives are to ; Identify the causes that prevent the proper teaching of the fundamentals of soccer in the eighth year students of basic education in urban public schools of the city of Loja, propose methodological strategies for teaching each of the basic fundamentals of soccer in the eighth year students of basic education in urban public schools of the city of Loja. The methodology is raised in the qualitative and quantitative , scientific method was used , the descriptive method to collect survey information was used , the checklist , and observation technique was used , the population comprises 150 eighth year male students and 3 teachers from Colegio Adolfo Valarezo , and 120 male students of the eighth year and 3 teachers from Colegio Manuel Cabrera Lozano , the results were structured in tables and graphs and each with its own analysis and interpretation assumptions hypothetical research that addresses the same as it performed through the analysis , interpretation and decision of each of the hypotheses raised as part of this process also allowed us to reach conclusions and recommendations.